The Application of Problem-Based Learning Methods to Improve Economic Learning Outcomes and Motivation - Khusaini, Khusaini; Lestari, Sri; Agustin, Nita Aulia (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
The aim of this study is to determine the effectiveness of the application of Problem-Based Learning methods in improving students’ learning outcomes at the eleventh grade of SMA Negeri 20 Tangerang Regency batch 2018/2019. This study used a quasi-experimental design and the techniques of collecting data were test, questionnaire, observation sheet, and document. The population in this study were 308 students consisted of students of eleventh grade in science 1 - 4 and eleventh grade in social science 1 – 4. This study used eleventh grade in science 2 and eleventh grade in science 4 as the sample that was taken non-randomly by using purposive sampling. The students’ learning motivation for economic subjects with the material about national income is considered good based on the t-test result. The value of t-test was 5,288 where tcount ttable (5,288 1,977). It could be concluded that there was a significant differences between students’ learning outcomes that used Problem-Based Learning method and those that used conventional method in economic subject of student national income material at the eleventh grade of SMA Negeri 20 Tangerang Regency. This research also found that Problem-Based Learning methods improved student’s motivation.